(3GdSQGL GdhgGL GdehVM dcd WGdH eMJGLs - (3CHh HcQ Hf Ydj Hf eMeO GdMOGO GdnqRHjOj , (B800 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf gPG cJGH CdaJg TQMG deNJUQ GdbOhQj ehVMG deTcdGJg eJhSWG Hjf GdEbdGd hGdEcKGQ ChVMJg dcd WGdH eMJGL hSejJg GdSQGL GdhgGL s
(3BNQgG (B:s
(3haj TQMg CeG EPG CbQVg OQGge eWdbI hde jTJQW Ydjg Pdc Ke cJH dg HgG GdeSJbQV Edi HdO BNQ de jcf Pdc ecQhgG dCfg de jTJQW GdefaYI aj ebGHd GdbQV hEfeGYd dg Pdc ef ZjQ TQW aUGQ cEQLGM GdejRGf YfO GdbVGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 67s
(3eYLe GdeDdajf (B1 / 441s
(3cTa GdXfhf (B2 / 1631s
(3GdHOQ GdWGdY (B1 / 166s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs